Donor–Recipient Matching Based on Predicted Indirectly Recognizable HLA Epitopes Independently Predicts the Incidence of De Novo Donor‐Specific HLA Antibodies Following Renal Transplantation. Issue 12 (28th July 2017) - Lachmann, N.; Niemann, M.; Reinke, P.; Budde, K.; Schmidt, D.; Halleck, F.; Pruß, A.; Schönemann, C.; Spierings, E.; Staeck, O.
Abstract : De novo donor‐specific HLA antibodies (dnDSA) are recognized as a risk factor for premature allograft failure. Determinants of DSA specificity are generated via the indirect allorecognition pathway. Here, we present supportive data for the relevance of predicted indirectly recognizable HLA epitopes (PIRCHE) to predict dnDSA following kidney transplantation. A total of 2787 consecutive kidney transplants performed between 1995 and 2015 without preformed DSA have been analyzed. De novo DSA were detected by single antigen bead assay. HLA epitope mismatches were determined by the HLAMatchmaker and PIRCHE approach and correlated in uni‐ and multivariate analyses with 10‐year allograft survival and incidence of dnDSA. The PIRCHE‐II score moderately predicted allograft survival. However, the predictive value of elevated PIRCHE‐II scores >9 for the incidence of dnDSA was statistically significant (p < 0.001). In a multivariate Cox regression analysis adjusted for antigen mismatch and HLAMatchmaker epitopes, the PIRCHE‐II score could be identified as an independent risk factor for dnDSA. The PIRCHE‐II score independently from the antigen mismatch and HLAMatchmaker epitopes could be revealed as being a strong predictor for dnDSA. PIRCHE may help to identify acceptable mismatches with decreased risk of dnDSA and thus improve long‐term renal allograft survival. Abstract : HLA epitope matching at the time of transplantation better predicts the development of de novo donor‐specific antibodies and long‐term allograft outcome than conventional antigen matching.